Beta Distribution in PERT Technique: An Analytical Evaluation for Project Management - Sahrawat, Shrruti (Journal of Global Economy, Business and Finance, 2026)
Schedule Management is one of the key aspects of project management in view to ensure how effectively and efficiently the work gets delivered. There are various software’s which are primarily used for the planning and scheduling of the activities with respect to various methodologies used. One of the widely used defined as Three Point Estimation and beta Distribution model. Three Points is a technique used by professionals in estimating. This technique use the three figures that are produced initially for every distribution that is required, based on prior experience or best-guesses. The first is a most likely (M)/best guess (BG) which is the average amount of work the task might take if the team member performed it 100 times. The second estimate is the pessimistic (P) estimate which is the amount of work the task might take if the negative factors they identified do occur. The third estimate is the optimistic (O) estimate which is the amount of work the task might take if the positive risks they identified do occur. You may use the beta distribution method to calculate the three point estimating. As the most likely scenario has a more significant impact on the outcome, you multiply the value by 4 while the overall divisor increases to 6 which is further versed in the paper